Teachers making sense of undocumented status and their responsibilities to undocumented students: A critical perspective. (February 2021) - Connery, Chelsea; Weiner, Jennie Miles
Abstract: This interpretive qualitative study explores how teachers' socialization contributes to their sensemaking of undocumented status and their responsibilities to undocumented students. Analyses of interview data revealed three key themes in teachers' socialization (early experiences with diversity, preparation experiences, and professional development) influencing whether their sensemaking reflected what we identified as status-negative, status-blind, or status-allied perspectives. Findings indicate without formal learning opportunities surrounding immigration and undocumented students, these issues are likely to be ignored or left to teachers' individual, and possibly problematic, efforts. Implications for teacher education and professional development are discussed. Highlights: Teachers' sensemaking ranged from status-negative to status-blind to status-allied. Differences in sensemaking were associated with varied socialization experiences. Without critical formal learning opportunities teachers rely on socialized schema. Socialization by dominant discourse is related to status-negativity and -blindness.